2020
DOI: 10.3390/medicina56100500
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Patients on Hemodialysis with Erectile Dysfunction

Abstract: Background and objectives: In patients on hemodialysis, erectile dysfunction is an independent mortality factor. This study aimed to determine the risk factors that affect the survival of hemodialysis patients with erectile dysfunction. Materials and Methods: During a seven-year period, erectile dysfunction was identified among the fatalities reported in patients receiving chronic hemodialysis, on the basis of the International Index of Erectile Function questionnaire. The study covered 70 patients of mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…In the study by Stolic et al, the survival of patients on hemodialysis with ED (an independent risk factor for mortality) was assessed: from the cohort of 70 patients, 60% (n = 42) died during the study period (mean age: 57 ± 6.8 years). Overall, their study highlighted that preserved diuresis, lower severity of cardiovascular illness, less-thick intima media in the carotid arteries, and high-quality hemodialysis were all associated with improved survival in patients with hemodialysis [30]. Bener et al compared the prevalence of ED among men with normal blood pressure and men with hypertension in Qatar, using the International Index of Erectile Function (IIEF) as a scale of sexual dysfunction: among n = 296 patients with hypertension, 66.2% had ED, while this ratio was much lower among normotensive patients (p < 0.001); additionally, age, highest level of education, presence of T2DM, and current occupation all had significant influence on the level of sexual dysfunction [31].…”
mentioning
confidence: 99%
“…In the study by Stolic et al, the survival of patients on hemodialysis with ED (an independent risk factor for mortality) was assessed: from the cohort of 70 patients, 60% (n = 42) died during the study period (mean age: 57 ± 6.8 years). Overall, their study highlighted that preserved diuresis, lower severity of cardiovascular illness, less-thick intima media in the carotid arteries, and high-quality hemodialysis were all associated with improved survival in patients with hemodialysis [30]. Bener et al compared the prevalence of ED among men with normal blood pressure and men with hypertension in Qatar, using the International Index of Erectile Function (IIEF) as a scale of sexual dysfunction: among n = 296 patients with hypertension, 66.2% had ED, while this ratio was much lower among normotensive patients (p < 0.001); additionally, age, highest level of education, presence of T2DM, and current occupation all had significant influence on the level of sexual dysfunction [31].…”
mentioning
confidence: 99%
“…Similarly, in a past study with 659 women receiving chronic hemodialysis, the authors reported that of the six FSFI‐defined domains of sexual function, satisfaction was the least impaired [6]. Indeed, in a study among women from the general medical population, the authors also reported while nearly half of study participants had FSFI‐defined sexual dysfunction, >80% of them were satisfied with their sexual function [46].…”
Section: Discussionmentioning
confidence: 94%
“…Notably, significant increase in overall prevalence and severity of erectile dysfunction among our male hemodialysis patients during the COVID-19 pandemic is particularly important, given that erectile dysfunction is considered a surrogate marker of endothelial damage and an early marker for cardiovascular disease and predicts cardiovascular mortality [6,47,48]. In addition to being a distressing symptom in itself, erectile dysfunction has increasingly become recognized as a risk marker for potentially life-threatening cardiovascular disease events and premature death, including hemodialysis patients [6,49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations